2021
DOI: 10.1021/acs.inorgchem.1c02198
|View full text |Cite
|
Sign up to set email alerts
|

Construction of MOF/COF Hybrids for Boosting Sunlight-Induced Fenton-like Photocatalytic Removal of Organic Pollutants

Abstract: In this work, a metal−organic framework (MOF) material of NH 2 -MIL88B was hybridized with TpPa-1-COF through covalent bonding, and the hybrid was subsequently employed for the degradation of Rhodamine B (RhB) and tetracycline (TC) by simulated sunlight-induced Fenton-like exciting H 2 O 2 . The obtained results show that its photocatalytic activity is much better than those of its parent MOF and covalent organic framework (COF). Moreover, it is much higher than that of bare photocatalysis without Fenton-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…For example, we constructed MoS 2 /COF and metal−organic framework (MOF)/ COF heterojunctions for the photocatalytic removal of organic pollutants. 41,42 Yao et al fabricated a covalent-bond-connected reduced graphene oxide (rGO)/COF heterojunction for enhanced H 2 evolution. 30 The above heterojunctions prepared ZnAgInS is an intriguing visible-light-active photocatalyst with a unique local atomic arrangement and electronic structure, which is favorable for light absorption and charge migration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, we constructed MoS 2 /COF and metal−organic framework (MOF)/ COF heterojunctions for the photocatalytic removal of organic pollutants. 41,42 Yao et al fabricated a covalent-bond-connected reduced graphene oxide (rGO)/COF heterojunction for enhanced H 2 evolution. 30 The above heterojunctions prepared ZnAgInS is an intriguing visible-light-active photocatalyst with a unique local atomic arrangement and electronic structure, which is favorable for light absorption and charge migration.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[121][122][123][124] Based on this view, Zhang et al reported a highly active Fenton-like hybrid photocatalyst of NH 2 -MIL88B@TpPa-1-COF, which was constructed according to the process in Figure 7a. [125] The photocatalytic performance of as-synthesized hybrid materials was evaluated by the photocatalytic degradation of tetracycline (TC). The result showed that NH 2 -MIL88B@TpPa-1-COF (40:63 mg 1,3,5-triformylphloroglucinol, 48 mg p-phenylenediamine, and 40 mg NH 2 -MIL88B) exhibited the highest TC degradation of 86%.…”
Section: Photocatalytic Degradationmentioning
confidence: 99%
“…[ 45 ] Subsequently, other MOF@COF hybrid materials have been reported. [ 32,46 ] However, maybe this growth sequence is not optimal due to the tiny cell size of MOFs and the mesoporous structure of COFs. The common characteristic of these reported MOF/COF hybrid materials is that the performance relies on the interfacial interaction between the MOF and COF layers, where the limited contact interface in MOF@COF hybrid materials restricts their photocatalytic performance for further improvement.…”
Section: Introductionmentioning
confidence: 99%